Production and Composition of Pyrogenic Dissolved Organic Matter From a Logical Series of Laboratory-Generated Chars - Bostick, Kyle W.; Zimmerman, Andrew R.; Wozniak, Andrew. S.; Mitra, Siddhartha; Hatcher, Patrick G. (Frontiers in Earth Science, 2018)
Though pyrogenic carbon (pyC) has been assumed to be predominantly stable, degradation and transfers of pyC between various pools have been found to influence its cycling and longevity in the environment. Dissolution via leaching may be the main control on loss processes such as microbial or abiotic oxidation, mineral sorption, or export to aquatic systems. Yet, little is known of the controls on pyrogenic dissolved organic matter (pyDOM) generation or composition. Here, the yield and composition of pyDOM generated through batch leaching of a thermal series of oak and grass biochars, as well as several non-pyrogenic reference materials, was compared to that of their parent solids. Over 17 daily leaching cycles, biochars made from oak at 250 to 650° C released decreasing amounts of C on both a weight (16.9 to 0.3%, respectively) and C yield basis (7.4 to 0.2% C, respectively). Aryl-C represented an estimated 32 to 82% of C in the parent solids (identified by 13C-NMR), but only 7 to 38% in the leachates (identified by 1H-NMR), though both increased with pyrolysis temperature. PyC, often operationally defined as condensed aromatic carbon (ConAC), was quantified using the benzenepolycarboxylic acid (BPCA) method. Tri- and tetra-carboxylated BPCAs were formed from non-pyrogenic reference materials, thus, only penta- and hexa-carboxylated BPCAs were used to derive a BPCA-C to ConAC conversion factor of 7.04. ConAC made up 24 to 57% of the pyrogenic solid C (excluding the 250 °C biochar), but only about 9 to 23% of their respective leachates’ DOC, though both proportions generally increased with pyrolysis temperature. Weighted BPCA compound distributions, or the BPCA Aromatic Condensation (BACon) Index, indicate that ConAC cluster size increased in pyrogenic solids but not in leachates. Additional evidence presented suggests that both aromatic cluster size and O-containing functional group contents in the pyrogenic solid control pyC solubility. Overall, pyDOM was found to be compositionally dissimilar from its parent chars and contained a complex mixture of organic compound groups. Thus, it is expected that estimates of dissolved pyC production and export, made only by detection of ConAC, are too low by factors of 4 to 11.